Динамическая модель тормоза с контактным возбуждением фрикционных колебаний - Коптовец, А. Н. (НТУ "ХПИ", 2014)
Разработана математическая модель возбуждения и взаимодействия фрикционных колебаний в колодочно-колесном тормозе при наличии конструктивных связей и распределении контактных усилий по деформируемым шероховатым поверхностям. Для внедрения результатов выполнена классификация задач по разработке тормозов шахтного подвижного состава как трибологической системы, в которой коэффициент трения обладает агрегатными свойствами. Динамическая модель тормоза использует колебательную систему с двумя степенями свободы. Конструктивные связи колодки моделируют два упругодемпфирующих элемента Фойхта. Компонента локальных сил взаимодействия микронеровностей контакта считается пропорциональной величине их взаимного перекрытия. Трение между контактирующими поверхностями описывается одночленным законом Амонтона.

A mathematical model of frictional oscillation excitation and interaction in a tread and wheel brake has been developed in terms of availability of ligaments and distribution of contact forces over deformable rough surfaces. To implement the results, problems of pit rolling stock brakes have been classified as a tribological system. Within the system, the friction coefficient has aggregate properties. The dynamic model of the brake uses an oscillating system with two degrees of freedom. The wheel has constant angular velocity. The tread ligaments are modeled by two Voigt elements. It is usual to neglect the tread and wheel surface curvature. Under certain conditions, the availability of Voigt elements in the model results into a coordinate relation between the normal oscillations and tangential ones. The normal components of the local forces arising at the microroughness contact points are considered proportional to the area of microroughness overlap. The friction between the contact surfaces is described by mononomial Amonton's law.
Dynamic brake model with contact excitation of frictional oscillations
Keywords: колодочно-колесные тормоза; фрикционные колебания; шахтный подвижной состав; коэффициент трения; динамическая модель тормоза; деформируемые шероховатые поверхности; контактирующие поверхности; конструктивные связи колодки; колодки; brakes; dynamics; friction; oscillations; roughness; contact surface; efficiency